History in Cultural Studies. War Excesses in the Former Dutch Indies - Westerlaken, Rodney (An1mage Jurnal Studi Kultural, 2017)
Currently the excesses of the colonial war between The Netherlands and Indonesia in the former Dutch Indies are being re-evaluated and interpreted in The Netherlands. More and more reports, photos and confessions appear showing a different truth than the one that is generally accepted in The Netherlands.  Marx said that people make history, but never in conditions of their own making. This essay evaluates the perspective of cultural studies in a historical context.